Impact pathways to research translation: canvases, toolkits and best practices from EU R&I projects - Kryzhanivska, Kateryna (Henry Stewart Talks, 2025)
The global meaning of impact, Relevance of research context, Growing and scaling research impact, Examples of engagement with impact-worthy areas of research, Mapping research impact pathways, Scoping emerging research context